Neudamm 2 (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
108 JPEG files of second visit to Neudamm research and training farm near Windhoek
Keywords: Sheep-shearing; Education; Agriculture; Karakul sheep; Germany; Karakul Farming; Karakul Sheep Industry